2004
DOI: 10.1021/np0498915
|View full text |Cite
|
Sign up to set email alerts
|

Hemisynthetic Secofriedelane Triterpenes with Inhibitory Activity against the Growth of Human Tumor Cell Lines in Vitro

Abstract: Seco acids 7 and 9 and hydroxylated analogues 5 and 6 derived from friedelane triterpenes were synthesized stereoselectively in high yields. Compounds 5-9 were evaluated for their ability to inhibit in vitro the growth of three human tumor cell lines, MCF-7 (breast adenocarcinoma), NCI-H460 (non-small cell lung cancer), and SF-268 (CNS cancer). Only compounds 7 and 9 were found to possess significant growth inhibitory effects, exhibiting GI(50) values that range from 24.6 to 32.8 microM and 10.9 to 17.6 microM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…The 13 C NMR data of 3 were well comparable with those of 4˛-hydroxyfriedel-3-one, 8 in which the assignment of C-1 (υ C 29.7 ppm, t) in the literature 8 was revised to υ C 17.8 (t, C-1) ppm according to HMBC correlation. The˛-hydroxyl substitution of 3 could be clarified from the 13 C data of C-10 (υ C 52.3 ppm, d) in contrast with C-10 (υ C 57.8 ppm, d) of -hydroxyl substitution.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The 13 C NMR data of 3 were well comparable with those of 4˛-hydroxyfriedel-3-one, 8 in which the assignment of C-1 (υ C 29.7 ppm, t) in the literature 8 was revised to υ C 17.8 (t, C-1) ppm according to HMBC correlation. The˛-hydroxyl substitution of 3 could be clarified from the 13 C data of C-10 (υ C 52.3 ppm, d) in contrast with C-10 (υ C 57.8 ppm, d) of -hydroxyl substitution.…”
Section: Resultssupporting
confidence: 61%
“…Our preliminary examination of the stem and bark of H. tiliaceus L., collected from mangrove forests in Hainan Island, South China, resulted in the isolation and characterization of nine triterpenoids. The compounds could be classified into oleanane-types, including oleanolic acid, 4 3ˇ-O-(phydroxy-Z-cinnamoyl)oleanolic acid, 5 3ˇ-O-(p-hydroxy-Ecinnamoyl)oleanolic acid, 6 and friedelane-types involving 27-oic-3-oxo-28-friedelanoic acid (1), 3˛-hydroxyfriedelane-2-one (2), 7 4˛-hydroxyfriedelane-3-one (3), 8 friedelin (4), 7,9,10 epifriedelanol (5), 10 -12 and pachysandiol A (6), 10 of which 1 was determined as a new compound through extensive 2D NMR data analyses. The known compounds were identified by NMR data analyses and by comparison of their spectroscopic data with those in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that friedelin, as well as its derivatives, have a variety of properties including analgesia and anti-inflammatory abilities, anti-cancer activity, anti-bacterial activity and vascularising agent (Frame, 2003;Moiteiro et al, 2001Moiteiro et al, , 2004Nakamura et al, 1997;Pires et al, 2009;Zhang et al, 2006). Furthermore, it has the potential to be utilized in pharmaceutical products or in functionalized food for treating cardiovascular and cerebrovascular tumors and other diseases (Zhang et al, 2006).…”
Section: Compoundsmentioning
confidence: 99%
“…Triterpenes such as oleanolic and ursolic acids have fluidity-modulating effects on liposomal membranes (Han et al 1997). Semisynthetic derivatives of friedelin (20), including epifriedelinol acetate (17), have been described as exhibiting low-moderate cytotoxicity to Sf9 and CHO cells (Moiteiro et al 2006) and also as inhibitors of human lymphocyte and cancer cell proliferation (Moiteiro et al 2001(Moiteiro et al , 2004. Other friedelane, oleanane, lupane, and ursane triterpenes have also been reported as tumoral cell growth inhibitors (Setzer and Setzer 2003;Chang et al 2004;Fu et al 2005;Mukherjee et al 2006).…”
Section: Postingestive and Cytotoxic Effectsmentioning
confidence: 99%